(untitled) (Journal of the College of Languages (JCL), 2019)
Aleksandr Isayevich Solzhenitsyn was born in 1918 in Kislovodsk. His father was educated, and despite his peasantry origin, he got a university degree. Unfortunately, however, Solzhenitsyn could not recognize his father, for he died before his birth. Solzhenitsyn was accused of being an opponent to the Soviet Union due to his activities of that time. He was exiled to a forced labour camp for eight years, on the surroundings of Moscow. He spent three years in Kazakhstan, and was sent to the life exile. He was set free in 1956. He worked as a teacher in in rural schools in Vladimir and then in Rezhran. His greatest works were in the reign of Kherchov, and in 1962 appeared his story under the title of "One day in the life Ivan Denisovich". The most prominent event in his life was his award of Nobel Prize, which he could not receive because of being an opponent to the Soviet Union, but after his expulsion from Russia, he was given the Prize. As to his words about himself, oppression increased proportionally with the appearance of my works. His works reached their climax after he was set free in 1973. He wrote his novel "The Gulag Archipelag". Аннотация Жизнь философского писателя, цель которого заключалась в достижении справедливости, заключалась в том, чтобы выявить реальную жизнь русского народа, И личная жизнь фактов, которые, как известно, сравнивают некоторых персонажей, которые стремятся к справедливости и свободе. Другой в прекрасном художественном стиле и глубоком значении указывает на потенциальный язык писателя, , И выступать за противоречивые идеи, связывая события с моделями людей и делая каждого из этих персонажей конкретной судьбой и влиянием в виртуальной реальности идеологии. он объяснил В своих сочинениях, что у русского народа нет исчерпывающего взгляда на его историю, и он продолжался несколько поколений. Вдохновением писателя были одни и те же люди и конфликт между личной сущностью и рушащейся ложью, создавая гармоничную картину повествования, Таким образом, обогащая русского читателя и показали художественных и литературных фактов и специальных идей о структуре российского общества.